2014
DOI: 10.1007/s00122-014-2389-5
|View full text |Cite
|
Sign up to set email alerts
|

Linkage disequilibrium and association analysis of stripe rust resistance in wild emmer wheat (Triticum turgidum ssp. dicoccoides) population in Israel

Abstract: Rapid LD decay in wild emmer population from Israel allows high-resolution association mapping. Known and putative new stripe rust resistance genes were found. Genome-wide association mapping (GWAM) is becoming an important tool for the discovery and mapping of loci underlying trait variation in crops, but in the wild relatives of crops the use of GWAM has been limited. Critical factors for the use of GWAM are the levels of linkage disequilibrium (LD) and genetic diversity in mapped populations, particularly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…GWAM has so far only been used for the dissection of disease resistance in DIC, using a collection of unrelated DIC genotypes (119). Although DIC is considered to be a selfer, Sela et al (119) revealed that LD decayed fast along DIC chromosomes and reached the background level within 1 cM, suggesting that GWAM can also be used for gene discovery and in the mapping of drought-related traits in DIC. GWAM was successfully used to identify a maize NAC gene (ZmNAC111), which can enhance drought tolerance by improving water-use efficiency and induce upregulation of droughtresponsive genes under water stress (79).…”
Section: Wwwannualreviewsorg • Evolution and Adaptation Of Wild Emmmentioning
confidence: 98%
See 1 more Smart Citation
“…GWAM has so far only been used for the dissection of disease resistance in DIC, using a collection of unrelated DIC genotypes (119). Although DIC is considered to be a selfer, Sela et al (119) revealed that LD decayed fast along DIC chromosomes and reached the background level within 1 cM, suggesting that GWAM can also be used for gene discovery and in the mapping of drought-related traits in DIC. GWAM was successfully used to identify a maize NAC gene (ZmNAC111), which can enhance drought tolerance by improving water-use efficiency and induce upregulation of droughtresponsive genes under water stress (79).…”
Section: Wwwannualreviewsorg • Evolution and Adaptation Of Wild Emmmentioning
confidence: 98%
“…Most of the Pst resistance was found in the northern part of Israel (22,119), where humid and cooler climatic conditions are more favorable to Pst development. Environmental conditions that are favorable to the onset of the disease seem to play a key role in development and maintenance of high R-gene diversity in the DIC-Pst pathosystem.…”
mentioning
confidence: 98%
“…AM uses linkage disequilibrium (LD) between alleles within diverse populations to identify markers associated with particular traits [16]. Recently, AM has been used to identify marker-trait associations in higher plants including disease resistance in potatoes [17] and wheat [1823]. …”
Section: Introductionmentioning
confidence: 99%
“…NGS mediated discovery of SNPs was previously utilized for the fine mapping of a grain protein content locus in durum wheat52. Although the SNP frequencies reported here are relatively lower than the study of Sela et al 51, and, another study reporting SNP discovery via NGS in two Ae. tauschii accessions34, the accumulation of high-throughput NGS data is likely to play pivotal role in gene discovery and mapping in wild emmer wheat that can further be implemented into wheat improvement.…”
Section: Discussionmentioning
confidence: 51%
“…The contrasting drought tolerances of TR39477 and TTD-22 potentiates the use of the SNPs for novel molecular marker design to aid in genetic and physical mapping of genomic drought-resistance loci. Through effective genotyping of wild populations these SNPs could be useful for gene discovery and mapping, as demonstrated by the SNP-based genome-wide association mapping of stripe rust resistance reported recently51. NGS mediated discovery of SNPs was previously utilized for the fine mapping of a grain protein content locus in durum wheat52.…”
Section: Discussionmentioning
confidence: 99%